2007
DOI: 10.4319/lo.2007.52.1.0286
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent mixing and phytoplankton spring bloom development in a deep lake

Abstract: A one-dimensional (1-D) mechanistic phytoplankton model combined with a 1-D hydrodynamic model was applied to simulate phytoplankton growth during winter and spring in deep monomictic Upper Lake Constance. Modeled chlorophyll a concentrations agree well with data from the 8-y time period considered. In particular, the interannual variation in the timing of phytoplankton growth is adequately simulated by the model. The onset of phytoplankton blooms in Upper Lake Constance is not sensitive to variations in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
109
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(119 citation statements)
references
References 41 publications
9
109
0
1
Order By: Relevance
“…This is an experimentally backed approach (Norberg and DeAngelis 1997) commonly used in minimal models of phytoplankton-zooplankton interaction (Scheffer et al 2001;Peeters et al 2007). The algal growth rate, which is dependent on water temperature, light intensity I (W m 22 ), silicate concentration Si (mg L 21 ), and phosphorus cell quota Q (mg P mm 23 ), was calculated as…”
Section: Symbolmentioning
confidence: 99%
“…This is an experimentally backed approach (Norberg and DeAngelis 1997) commonly used in minimal models of phytoplankton-zooplankton interaction (Scheffer et al 2001;Peeters et al 2007). The algal growth rate, which is dependent on water temperature, light intensity I (W m 22 ), silicate concentration Si (mg L 21 ), and phosphorus cell quota Q (mg P mm 23 ), was calculated as…”
Section: Symbolmentioning
confidence: 99%
“…In deep lakes, the onset of the spring phytoplankton bloom is coupled to the onset of thermal stratification, i.e. the transition from strong to weak turbulent mixing (Peeters et al 2007b), which increases the mean light exposure of the cells, but limits subsequent nutrient supply (Wetzel 2001;Winder and Schindler 2004b). Studies in European lakes found that the duration of deep mixing after warmer winters decreased and earlier lake stratification promoted earlier onset of the phytoplankton bloom in spring (Weyhenmeyer et al 2002;Peeters et al 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…Henson et al (2006) studied the effect of meteorological conditions on interannual variability in timing and magnitude of spring bloom in the Irminger Basin, North Atlantic. Peeters et al (2007b) analyzed to what extent the onset and early development of the spring phytoplankton bloom depends on seasonal changes in turbulent mixing, solar radiation and water temperature. Henson (2007) pointed out that the onset of water column stability is closely linked to the timing of the phytoplankton spring bloom.…”
Section: Introductionmentioning
confidence: 99%